Vocational training program for Agricultural Machinery Mechanics - CGIAR Research Program on Rice (2019)
Training course available at Don Bosco in Battambang. By 2017 24 agricultural engineers have graduated and 23 apprentices completed their training and found employment in the agricultural industry and are contributing to a more sustainable mechanization. This training course is now available for uptake by other users.